2007
DOI: 10.1093/ndt/gfm056
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus 8 infection in kidney transplant patients from an area of northwestern Italy (Piemonte region)

Abstract: Background. Human herpes virus 8 (HHV-8) infection is associated with Kaposi sarcoma (KS) and other neoplastic and non-neoplastic manifestations. A strong association between HHV-8 and KS has been evidenced in transplant recipients, particularly kidney recipients. Methods. We have investigated the HHV-8 seroprevalence by an immunoenzymatic assay in 408 patients awaiting kidney transplantation and in the corresponding 356 donors; moreover, we have tested for the presence of HHV-8 DNA by nested PCR in available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Higher detection rates of HHV‐8 DNA and plasma anti‐HHV‐8‐IgG were found in the hemodialysis patients compared to a sample of apparently healthy people (blood donors and pregnant women, which for purposes of analysis were combined as a single group). This result supports previous data showing the comparatively high prevalence of plasma anti‐HHV‐8 in patients with chronic renal failure when compared to controls from the same country [Qunibi et al, 1998; Regamey et al, 1998; Hsu et al, 2002; Bergallo et al, 2007; Caterino‐de‐Araujo et al, 2007; Lonard et al, 2007; Jalilvand et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Higher detection rates of HHV‐8 DNA and plasma anti‐HHV‐8‐IgG were found in the hemodialysis patients compared to a sample of apparently healthy people (blood donors and pregnant women, which for purposes of analysis were combined as a single group). This result supports previous data showing the comparatively high prevalence of plasma anti‐HHV‐8 in patients with chronic renal failure when compared to controls from the same country [Qunibi et al, 1998; Regamey et al, 1998; Hsu et al, 2002; Bergallo et al, 2007; Caterino‐de‐Araujo et al, 2007; Lonard et al, 2007; Jalilvand et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies of HHV‐8 infection in hemodialysis patients were confined exclusively to determining the prevalence of anti‐HHV‐8 antibodies [Almuneef et al, 2001; Andreoni et al, 2001; Hsu et al, 2002; Di Stefano et al, 2006; Bergallo et al, 2007]. In the present study, conducted among Saudi Arabian patients with chronic renal failure receiving hemodialysis, the extent and diversity of oral HHV‐8 shed in saliva and oral cells were investigated, in addition to anti‐HHV‐8 seroprevalence determination.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing HHV-8 seropositivity in the transplant population in endemic areas has been reported in the range of 4.9% to 16% [117][118][119]. The frequency of KS in solid-organ transplant recipients parallels the seroprevelance of HHV-8 infection in different regions of the world.…”
Section: Clinical Manifestations Of Hhv-8: Oncogenic and Non-oncogenimentioning
confidence: 99%
“…Following initial infection, they can be maintained, in a dormant state, in the kidneys and lymphocytes. This family of viruses includes BK virus (BKV), JC virus (JCV), and simian virus 40 (SV40), all of which have been clinically observed in both normal and immunocompromised adults, such as those with AIDS and transplant recipients (Bergallo et al 2007). Through polymerase chain reaction (PCR) and DNA sequence analysis, it was observed that heightened combined levels of BKV, JCV, and SV40 were significantly more frequent (67 %) in postmortem brains of individuals having had ASD than in controls (23 %).…”
Section: Animal Analogues For Human Subjects With Asdmentioning
confidence: 99%